PENGARUH KUALITAS DAN CITRA PRODUK TERHADAP KEPUASAN PELANGGAN COCA-COLA DI KOTA MADIUN - Citaningtyas Ari Kadi, Dian (Widya Warta, 2018)
The observation was aimed at testing the impact of product quality and product image on customer satisfaction. The research population were everyone who had ever drunk Coca-Cola. The research used purpose sampling, namely a sampling technique because of some consideration.The sum of the samples were 10; the samples were enough since there were only 2 independent variables. The samples were collected with questionnaire and tested with the SPSS. The research results show that the product quality and the product image have positive impact on customer satisfaction.